Effects of prior knowledge and lesson outline on note taking and test scores - Olmos, Oscar Lasig (2008)
Three intact classes of first year high school students were randomly assigned to three environmental conditions for note-taking, forming the lesson outline group, the control group, and the prior knowledge group. The study compared the mean scores on notes and posttests of the three groups after attending a videotaped lecture for their Social Studies class. The study also investigated on the relationship between notes and test scores. It was revealed that hight-test scorers in the immediate and delayed posttest have significantly more information units than low-test scorers. Means of the total notes scores of high and low test scores were significantly different in the immediate posttest and in the delayed posttest. These results suggest the relative value of independent data in students' notes vis-a-vis the two functions of note taking.